Determinants of Spending Efficiency for Education and Health Functions - Siti Sriningsih; Haryanto, Tri; Solihin, Achmad (Universitas Negeri Semarang, 2024)
Government spending on education and health is mandated and regulated by law. The increase in education and health spending makes it necessary to study the analysis of the determinants of the efficiency of education and health expenditures in the districts and cities of the province of West Nusa Tenggara during 2012–2021. The approach used is in two stages. The first efficiency score is obtained by deployment Data Analysis (DEA) analysis, and the second stage is using Tobit to analyze the determinants of efficiency in each expenditure. The results of the first stage show that the average technical efficiency score for education spending is inefficient, while the technical efficiency score for health spending is efficient. Furthermore, for the second stage, the results show that the government's ability to finance development expenditures, population density, income inequality of the population, the ratio of junior high school student teachers, and the ratio of high school student teachers affect the efficiency of spending on the education function. Furthermore, the determinants of the efficiency of health spending based on Tobit's results are population density, income inequality of the population, and the ratio of health workers affecting spending on health functions.